Are the Most Dominant Affecting Stock Prices Other Than ROE? - Junaeni, Irawati (AIBPM Publisher, 2019)
There are several ways that companies can use in obtaining external funds, one of which is the capital market. Stock is one of the most popular capital market instruments. Stock prices are often used as a reference in investing. Stock prices can rise and fall depending on supply and demand in the capital market. This study aims to determine the variables that influence stock prices in retail companies listed on the Indonesia Stock Exchange (IDX). The technique used in this study was purposive sampling. This study also uses multiple linear regression analysis. The results of the research partially show that the Return on Equity variable and sales growth have a significant influence on stock prices, while the Total Asset Turn Over and Accounts Receivable Turnover have no significant effect on stock prices. Simultaneously, Return on Equity, sales growth, Total Asset Turn Over, and Accounts Receivable Turnover have a significant effect on stock prices with a coefficient of determination of 62.04%.